Evaluation of the Corrosion Behavior on Austenitic Stainless Steels in Artificial Oil Field Formation Water using Potentiodynamic and Potentiostatic Electrochemical Techniques (Global Journals of Research in Engineering, 2023)
Objective The main objective of this research was to evaluate the corrosion resistance of some austenitic and super austenitic stainless steel when immersed in an aqueous solution of artificial oil field formation water saturated with CO2 and also without CO2 With these two simulated situations the pH effect of the solution on the corrosion resistance of the alloys was studied Methods Samples of austenitic and super austenitic stainless steels previously characterized by x-ray diffraction using synchrotron light were used in this research Two electrochemical techniques one potentiodynamic and the other potentiostatic were used to investigate the effect of the solution on the corrosion behavior of the samples The linear polarization test was used to evaluate the CO2 corrosion resistance of the alloys in artificial oil field formation water The potentiostatic technique potential step was used to assess the influence of the solution without CO2 on the corrosion resistance of the alloys thus varying the pH of the electrolyte Scanning Electron Microscopy SEM was used to observe the type of corrosion on the surface of the samples Results The results indicated that the type of corrosion found on the surface of the alloys was pitting corrosion The pH effect of the solution artificial oil field formation water influenced the pits shape The conventional austenitic steels showed to have low corrosion resistance in chloride-containing environment The super austenitic stainless steels presented a high corrosion resistance in the solution with and without CO2 No pits or micro pits were observed on their surfaces by SEM Conclusion From the results obtained it was evident that the conventional austenitic stainless steels are not a good choice in severe environments like those found in the pre-salt region The super austenitic stainless steels showed to be a good option in CO2-containing environments mainly in aqueous solution with a high content of chloride
Keywords: austenitic stainless steels; CO2 corrosion resistance; aqueous solution; pitting corrosion; potential step; passive layer